Critical Netizen Perceptions of Polri in Instagram Discourse on the Affan Kurniawan Case: A CMDA-Appraisal Study - Enlynia Retno; Faris Annas (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2026)
Social media comment sections provide spaces where users evaluate public institutions and negotiate institutional legitimacy. This study examines how critical perceptions of the Indonesian National Police (Polri) were expressed in comments on an @narasinewsroom Instagram post concerning the death of Affan Kurniawan. Using qualitative descriptive content analysis, the study applied quota purposive sampling to select 100 comments from 4,581 available comments, with 20 comments drawn from each of five perception categories. The comments were coded according to their perception category, primary Computer-Mediated Discourse Analysis-informed message form, and primary emotional-evaluative stance, and were subsequently interpreted through Appraisal Theory. Within the quota-balanced sample, questions and demands for transparency were the most frequently coded message form (27%), followed by figurative language, humor, and satire (25%), assertive and evaluative statements (22%), collective statements and calls for action (20%), and argumentative reasoning (6%). Cynicism was the most frequently coded emotional-evaluative stance (45%), followed by suspicion (25%), anger (18%), disappointment (10%), and empathy (2%). The Appraisal analysis showed that the comments combined Affect, Judgement, and Appreciation to evaluate police actors, institutional conduct, and the credibility of the investigation. The study demonstrates how critical institutional perceptions were linguistically and evaluatively constructed within a selected digital discourse corpus. Because the sample was deliberately balanced, the findings describe only the analyzed comments and should not be generalized to all comments on the post or to broader public opinion.